2013
DOI: 10.1186/1471-2164-14-776
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive meta QTL analysis for fiber quality, yield, yield related and morphological traits, drought tolerance, and disease resistance in tetraploid cotton

Abstract: BackgroundThe study of quantitative trait loci (QTL) in cotton (Gossypium spp.) is focused on traits of agricultural significance. Previous studies have identified a plethora of QTL attributed to fiber quality, disease and pest resistance, branch number, seed quality and yield and yield related traits, drought tolerance, and morphological traits. However, results among these studies differed due to the use of different genetic populations, markers and marker densities, and testing environments. Since two previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
203
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 210 publications
(223 citation statements)
references
References 49 publications
16
203
2
2
Order By: Relevance
“…A total of 151 staple length QTLs were reported over the entire genome except chromosomes C2 and C22 [91]. In total 12 marker-trait association for staple length were reported in earlier study [125].…”
Section: Staple Lengthmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 151 staple length QTLs were reported over the entire genome except chromosomes C2 and C22 [91]. In total 12 marker-trait association for staple length were reported in earlier study [125].…”
Section: Staple Lengthmentioning
confidence: 99%
“…A total of 25 QTLs conferring lint production were reported over the entire genome but none of the chromosome contained more than three QTLs [91]. Qin et al [125] reported 17 associated markers with lint percentage.…”
Section: Ginning Out Turn Percentagementioning
confidence: 99%
See 3 more Smart Citations